Anatomical changes in artificially inclined stem of naturally grown Pometia Pinnata and Dyera Costulata at Ayer Hitam Forest Reserve - Mohd Razik, Mohamad Zubair Azim (2018)
Tension wood is abnormal wood compared to normal wood. This research aimed to study the formation of the tension wood between the low density and medium density hardwoods in tropical rainforest species. This study was conducted at the Ayer Hitam Forest Reserved Forest, Puchong, Malaysia. The selected species for low density species is Jelutong (Dyera Costulata) and medium density is Kasai (Pometia Pinnata). The trees selected is artificially inclined for 30 ,60 and 120 days.The cambial marking was applied to the all selected tress using high DC pulse. The density, time taken, and the inclined angle is the major factor affecting the tension wood. The results showing there is varies of G-layers formed on the both species in the different time period. The conclusion is the Jelutong is easily formed compared to Kasai based on the anatomical characteristics.